Numerical and Experimental Study on Mode Identification Error Characteristics of Fan Noise - Xu, Kunbo; Liu, Cunliang; Tong, Fan; Qiao, Weiyang (Frontiers in Energy Research, 2022)
The influence of different test methods on the accuracy of mode recognition is not clear, and it is necessary to explore the error transfer characteristics in mode decomposition of fan noise. Numerical and experimental researches are carried out on the advantages and disadvantages of radial rake and axial microphone array in mode decomposition and error transmission character-istics. In the numerical study, the error transmission characteristics of different arrays are inves-tigated by adding random disturbances to the artificial sound field, so as to evaluate the applica-bility and limitations of the two typical arrays in mode recognition based on the error analysis theory. The mode recognition error of the single-stage axial flow fan is investigated experimen-tally using the designed radial rakes and axial arrays. The results show that although the radial rake can directly measure the radial distribution of the modal amplitude, it has a large error in the mode identification at low frequencies. Compared with the radial rake, axial array will be-come more advantageous in practical applications. The accuracy of the axial microphone array in mode recognition strongly depends on the axial spacing of the array measuring sensors. The small deviations in the mode identification when applying the two typical arrays are caused by the different signal-to-noise ratio of the sound pressure signals acquired by the two arrays and their discriminative sensitivities to the duct airflow.